Ageing and Community: Introduction to the Special Issue. (January 2014) - Provencher, Claudine; Keating, Norah; Warburton, Jeni; Roos, Vera
ABSTRACT Population ageing is one of the major contemporary issues facing societies across the world. Originally framed as a major social and economic challenge, demographic ageing is now beginning to be seen as offering huge potential to individuals as well as to their communities. It is this positive potential that we explore in this issue by utilising two key disciplinary approaches—social gerontology and social/community psychology. In this introduction, we argue that focus on only one or the other of these perspectives is limiting. Instead, a more critical approach is needed that incorporates the strengths of both disciplines in order to build a more complete and stronger understanding of ageing and community. Thus, a focus on social gerontology highlights ageing issues and explores the diversity of older people and their interactions with community. By incorporating a social/community psychology approach, there is potential to complement this body of work through a deeper level of analysis around community, as well as individual and relational dimensions. The result is a special issue that brings together these two perspectives to address some of the shortcomings of approaching ageing through solely one disciplinary lens. Copyright © 2013 John Wiley & Sons, Ltd.